PEMODELAN NUMERIK POLA ARUS PASANG SURUT DI TELUK BENOA, BALI - Edi Yastika, Putu; Suyanto, Hery; Hendrawan, I Gede (BULETIN FISIKA; Vol 13 No 2 (2012): BULETIN FISIKA, 2012)
Numerical modeling had been carried out patterns of tidal currents in the Benoa Bay, Bali using Princeton Ocean Model (POM) 2 dimensions.The results of modeling tidal currents generated by semidiurnal components (M2, S2) and diurnal components (K1, O1) were average of depths. Data modeling results once validated with observational data obtained value of Root Mean Square Percentage Error Approximation (RMSPEA) of 1.55 for current data and 0.39 for elevation data. Semidiurnal tidal component was the most dominant of all, M2 components produced the greatest flow velocity than other components of  0.43 m/s at the mouth of bay between Serangan Island and Benoa Cape  on flood towards ebb tide conditions. From the modeling results showed all component pattern of tidal currents occur strengthening of the current at the mouth of the bay between the island of Serangan and Benoa Cape.